Serum level of sialic acid (SA) and carbohydrate‐deficient transferrin (CDT) in type 2 diabetes mellitus with microvascular complications - Cylwik, Bogdan (J Clin Lab Anal, 2006)
Sialic acid (SA) is responsible for the composition of different isoforms of transferrin and is reported to be a marker of microvascular complications in type 2 diabetes mellitus. Therefore, we explored the serum concentration of SA, and the less sialylated isoforms of transferrin, termed carbohydrate‐deficient transferrin (CDT), in relation to the presence of microvascular complications in type 2 diabetes mellitus. We studied 21 patients with type 2 diabetes with microangiopathy and 22 patients without complications who were hospitalized at a diabetic clinic. The prevalence of microvascular complications was based on clinical history, fundoscopy, and laboratory tests. Blood samples were taken for measurements of SA, CDT, total transferrin, glucose, HbA(1c), fibrinogen, C‐reactive protein (CRP), and indicators of renal dysfunction (i.e., creatinine, urea, albumin excretion rate (AER), and glomerular filtration rate (GFR)). A rise in serum SA and a decrease in CDT concentrations were observed in both diabetic groups with and without complications, and there were no differences between the two groups of patients. There was a statistically significant correlation between serum SA and CDT in diabetic subjects with microvascular complications, but not in patients without such complications. This proves that the serum changes in CDT and SA levels in the course of type 2 diabetes mellitus are associated with each other in the presence of microangiopathy. J. Clin. Lab. Anal. 20:68–73, 2006. © 2006 Wiley‐Liss, Inc.